UPAYA MENINGKATKAN HASIL BELAJAR FIQIH MATERI TAYAMMUM DENGAN MENGGUNAKAN METODE DEMONSTRASI PADA SISWA KELAS IIIA MI NW KALIJAGA - Najwa, Safiatun; Hayaturraiyan, Hayaturraiyan (Jurnal al Muta'aliyah: Pendidikan Guru Madrasah Ibtidaiyah, 2022)
Abstract This research was motivated by the low learning outcomes of class III-A MI NW Kalijaga fiqh subject in Tayammum material. This was known based on the results of the study, namely the number of students who had not reached the KBM (71%). Where in the initial conditions of the pre-cycle, only 20 students achieved completeness (40%), namely only 8 students who achieved KBM and 12 students who had not completed KBM. Researchers are trying hard to make improvements in learning tayammum material through Classroom Action Research (PTK) using the Demonstration method through two cycles. The results showed that the improvement of learning using the Demonstration method has been carried out well, this can be seen from the increase in student learning outcomes in cycle I from 20 students to 13 students who have completed KBM, with a percentage (65%), and increased to 17 students with a percentage (85%) who completed the KBM in cycle II. Thus the improvement of fiqh learning on tayammum material using the Demonstration method can improve student learning outcomes. So the researcher decided to end the Classroom Action Research only up to cycle II.